Leksikologi Kata Tabu dalam Bahasa Indonesia - Gita Anggria Resticka; Erwita Nurdiyanto (Aksara, 2024)
Taboo expressions are one example of the growing use of figurative language. The word taboo (taboo) means actions that are prohibited or avoided. The focus of this research is verbal taboo expressions which are partial or complete prohibitions against the use of certain words, expressions, and topics in social interactions. This research discusses lexical items (taboo lexicon) in Indonesian, examining their origins, form and formation, fields, and semantic aspects of taboo vocabulary in Indonesian. The lexicological research aims to identify taboo vocabulary or lexicon based on semantic division (nouns, verbs, adjectives), usage division (frequency, general/local), activity division, and grammatical division. This study used a descriptive qualitative method. The object of this research is vocabulary or lexicon of taboo in Indonesian. The data were collected by basic o techniques of observation, that is observing to taboo words of Indonesian in dictionaries, books, etc., while the advanced technique uses note-taking techniques. The data of this research were analyzed by distribution and matching methods. The results of this research identified divisions of Indonesian taboo vocabulary in terms of sources of acquisition, semantic divisions, usage divisions, and field of activity divisions. This research identifies the grammatical formation of taboo words through the affixation process, reduplication, and composition. Apart from that, this research also identifies the semantic aspects of Indonesian taboo vocabulary.